Importance of social media marketing on SMEs in South Africa - Nadkar, Ashna (University of the Free State, 2023)
This research study illuminates the dynamics of social media marketing in the context of small and medium enterprises (SMEs) and provides insight into the qualitative aspects thereof. The prime objective of this research study was to investigate, through an in-depth qualitative analysis, how SMEs experience, conceptualise and apply social media marketing strategies in the contemporary business environment in which they find themselves. The research design adopted a qualitative approach by utilising in-depth interviews to gain an understanding of the experiences of SMEs. The motivations, challenges and results concerning social media marketing were uncovered by capturing the narratives of SME owners and managers. The research design adopted facilitated a holistic understanding of the experiences of SMEs when they engage with social media marketing. The study revealed the multifaceted nature of the obstacles encountered by SMEs, ranging from time constraints to the need to adapt to the fast-paced digital landscape. This research study underscores the pivotal role and transformative power of social media marketing for SMEs in the current digital space. The qualitative approach highlighted the nuances in the dynamics of the social media strategies of SMEs, emphasising the importance of tailoring the approaches that align with the distinct characteristics and objectives of each business. The research study concluded that SMEs should be encouraged to embrace the interactive nature of social media to foster meaningful connections with their target audience and establish a strong online presence. In essence, this research study reveals valuable insights into the qualitative dimensions of social media marketing within the landscape in which SMEs are situated. The purpose, design, findings and conclusions of this research study were addressed and a practical guide for SMEs looking to navigate the complexities of social media in a way that aligns with their specific objectives was also provided.
Dissertation(MBA (Business Administration))--University of the Free State, 2023
Keywords: Social media marketing; Small and medium enterprises (SMEs); Qualitative analysis; Customer engagement; Digital landscape